2018
DOI: 10.1177/0306312718778806
|View full text |Cite
|
Sign up to set email alerts
|

The epistemic culture in an online citizen science project: Programs, antiprograms and epistemic subjects

Abstract: In the past decade, some areas of science have begun turning to masses of online volunteers through open calls for generating and classifying very large sets of data. The purpose of this study is to investigate the epistemic culture of a large-scale online citizen science project, the Galaxy Zoo, that turns to volunteers for the classification of images of galaxies. For this task, we chose to apply the concepts of programs and antiprograms to examine the ‘essential tensions’ that arise in relation to the mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 44 publications
1
35
1
Order By: Relevance
“…This is similar to Luczak-Roesch et al's (2014) conclusion that citizen scientists can contribute to "coordination around hypothesis" and "serendipitous citizen-led discoveries" when using features of the Talk forum. However, unlike Kasperowski and Hillman (2018), we have not found instances of tensions among user groups in our material. This could be due to the smaller size of the forum and younger age of the project, but also might hint at a difference between the domains of natural sciences in Kasperowski and Hillman's study as opposed to the humanities in our study.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…This is similar to Luczak-Roesch et al's (2014) conclusion that citizen scientists can contribute to "coordination around hypothesis" and "serendipitous citizen-led discoveries" when using features of the Talk forum. However, unlike Kasperowski and Hillman (2018), we have not found instances of tensions among user groups in our material. This could be due to the smaller size of the forum and younger age of the project, but also might hint at a difference between the domains of natural sciences in Kasperowski and Hillman's study as opposed to the humanities in our study.…”
Section: Discussioncontrasting
confidence: 67%
“…This form of knowledge generation has led to several discoveries made by volunteers on the Zooniverse platform (e.g., Tinati et al 2015: 4072). Kasperowski and Hillman (2018) have found that the discussion forum of the oldest Zooniverse project, Galaxy Zoo, contains not only discoveries made by volunteers but also reveals tensions between project staff and volunteers as the volunteers develop their own interests. Thus, it becomes a crucial issue to further investigate the impact of VCS forums with regards to co-creation of knowledge, also between scientists and non-scientists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sociology, the involvement is often realized in the whole scientific process, so citizen scientists help formulate the research question, shape the design of a project, collect and analyze data and are even contributing in the publication of the results [15,16]. In humanities, the involvement is often located somewhere between the ecological and the sociological degree of involvement [17][18][19]. An overall definition of citizen science is still lacking, but first attempts have been made by different stakeholders [1,4,20,21].…”
Section: What Is Citizen Science?mentioning
confidence: 99%
“…This ever-expanding diversity suggests that it would be futile to insist on an institutional or epistemological unity of citizen science or to argue that citizen science is epistemologically distinct from other forms of science. Such modes of knowledge production as crowdsourcing and open-access collaboration certainly pose interesting epistemological questions, but they are not confined to citizen science (Kasperowski and Hillman 2018;Strasser et al science project. We believe that this perspective is a necessary step toward a productive discussion of citizen science in East Asia (and beyond).…”
mentioning
confidence: 99%